2020
DOI: 10.1002/jtr.2422
|View full text |Cite
|
Sign up to set email alerts
|

In search of fresher air: The influence of relative air quality on vacationers' perceptions of destinations' restorative qualities

Abstract: This study aimed to unveil the effects of relative air quality on vacationers' perceived destination restorative qualities. Using survey-based data and second-hand air quality data, our regression results showed a higher level of relative air pollution was associated with vacationers' lower evaluations of a destination's "physically away" quality.These effects were moderated by the number of visits to the destination and travel distance. We found that vacationers' evaluations of the "physically away" quality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Most of the studies analyzed refer to undifferentiated “total” visitor groups of nature-based tourism, including local recreationists and outside vacationers. They were often affluent or medium-income earners from developed countries or emerging countries, highlighting a positive relationship between affluence and interest in health and wellness [ 35 , 36 , 37 , 38 , 39 ]. This is unsurprising given the current perceptions of natural areas as a luxury, and it reflects a broader trend identified in travel literature wherein older people and subsistence income earners appear less likely to visit natural environments than younger people and medium-/high-level salary earners [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies analyzed refer to undifferentiated “total” visitor groups of nature-based tourism, including local recreationists and outside vacationers. They were often affluent or medium-income earners from developed countries or emerging countries, highlighting a positive relationship between affluence and interest in health and wellness [ 35 , 36 , 37 , 38 , 39 ]. This is unsurprising given the current perceptions of natural areas as a luxury, and it reflects a broader trend identified in travel literature wherein older people and subsistence income earners appear less likely to visit natural environments than younger people and medium-/high-level salary earners [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…All 19 articles agreed that natural areas could promote attention recovery and stress relief through high levels of positive emotions, low levels of negative emotions, and a sense of satisfaction with one’s quality of life. For visitors suffering from mood disorders and attention fatigue, immersive natural environments, such as forests with hiking trails, can provide enhanced opportunities for nature connectedness and place attachment and can positively impact the visitors’ mood and feeling of satisfaction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A noticeable industry that garnered much attention is that of tourism. Becken et al [10], Xu and Reed [48,49], and Yang and Chen [50], among others, emphasized the significant negative influences of atmospheric pollution on tourist arrivals and receipts in China. The agricultural losses due to air pollution are also substantial, as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Potential tourists have explicitly been aware of and concerned with the air pollution in China [10,47]. The tourists' perception of air pollution has apparently reduced their willingness to visit China and the trip satisfaction [48][49][50]. As tourism is an economic growth engine in numerous districts [51,52], air pollution depresses economic growth through its damage to tourism.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Previous research has consistently found that green and blue spaces are restorative environments that can release stress to promote individuals' health benefits (Völker & Kistemann, 2011). In addition, destinations with better air quality promote more wellness and satisfy tourists' experiences (Yang & Chen, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%